Developing transdisciplinary approaches to community energy transitions: An island case study. (November 2018) - Heaslip, Eimear; Fahy, Frances
Abstract: Within energy planning, technical methods and quantitative data are often key components in assessing energy demand and developing feasible scenarios to meet communities' energy needs. Designing and implementing a transdisciplinary research approach to community energy planning, which attempts to combine conventional energy engineering techniques with in-depth qualitative (conventional social sciences) approaches, can pose challenging methodological questions in theory and practice. The paper discusses the design and development of a transdisciplinary methodological framework for community energy planning. Focussing on an island community in the west of Ireland, the paper then examines the implementation of this framework which generated qualitative data through in-depth focus groups and problem-centred interviews to inform the design of technical energy plan scenarios, employing hybrid micro-grid system design software. The results section outlines some of the rich context and place specific, energy related empirical evidence that was generated and discusses the development of three energy scenarios for the island. Finally, drawing on participants' observations on the process, the concluding discussion offers a reflection on the possibilities and challenges of employing a transdisciplinary approach to community energy planning with a view to providing valuable insights for energy planners, policy makers and researchers embarking on future research in this space.